Data to the Malaysian liverwort flora, VI: Two new species from the family Lejeuneaceae - Lee, Gaik Ee; Pócs, Tamás; Schäfer-Verwimp, Alfons (Phytotaxa, 2026)
Two new species of Lejeuneaceae from Malaysia are described and illustrated herein. Colura sabahensis is found in Sabah (Malaysian Borneo) while Lejeunea pahangensis occurs in Pahang (Peninsular Malaysia). Both species were found growing as epiphyllous and epiphytic liverworts in montane forest habitats rich in bryophyte diversity. Colura sabahensis is characterized by an ovate to lanceolate lobule sac with papillose surface and with crest on some leaves. Underleaves bilobed almost their whole length, only 2–3 cells wide at base, and leaf cells with large trigones and intermediate thickenings (up to four per cell). The distinguishing characters of L. pahangensis are its autoicy, relatively large plants (up to 2.0 mm wide), large epidermal cells, imbricate leaf lobes with broadly rounded apices, involute free margin of leaf lobules with visible first tooth in situ, suborbicular to wider than long underleaves, and 5-keeled perianths with a 2–3 cells long beak.